RETRACTED: Post-COVID-19 investor psychology and individual investment decision: A moderating role of information availability - Jan, Naveed; Jain, Vipin; Li, Zeyun; Sattar, Javeria; Tongkachok, Korakod (Frontiers in Psychology, 2022)
This study aims to investigate the influence of psychological biases on the investment decision of Chinese individual investors after the pandemic of covid-19 with a moderating role of information availability. A cross-sectional method with a quantitative approach of research was employed to investigate the hypothesized relationships among variables. The survey questionnaire was applied to gather the data from individual investors who are investing in the Chinese stock market. Results indicated that overconfidence, representative bias, and anchoring bias have a significant and positive influence on investment decisions, however, the availability bias has a significant but negative effect on the investment decision. Moreover, findings indicated that information availability has a significant moderating role in the relationship of psychological biases with the investment decision. This study contributes to the body of knowledge regarding behavior finance, psychological biases, and investment decision in emerging stock markets. The findings of the present study improve the understanding that how investors' psychology affects their investment decisions.